Women Workers and the Trade Unions - Boston, Sarah, 1944- (Book collections on Project MUSE., 2015)
Updated with new chapters on 1987-1997 and 1997-2010 In this highly-praised book, Sarah Boston recounts the story of women workers from the early nineteenth century to the present day: the struggles and strikes, successes and failures in their strenuous efforts to organise and win recognition from employers and male trade unionists. Women Workers and the Trade Unions - now republished with the addition of two new chapters - is the only comprehensive account of this neglected overlap of women's history and labour history. In this enlightening history, Sarah Boston argues that male trade unionists' exclusionary treatment of women workers contradicted not only the socialist aims of most trade unions but also the very logic of trade unionism itself. The account is essential reading for anyone concerned with the history of industrial relations, but also with the history of feminism and of women in the workplace. This new and updated edition includes a new preface by Frances O'Grady, as well as the two new chapters by Sarah Boston. The new chapters cover the period from 1987 to 2010, exploring the specific struggles of that period, and women's ongoing fight for equal rights and equal pay in the post-Thatcher period and under New Labour.